Jú onze e 24: pretextos, textos e contextos de atores drag-queens em Goiânia (GO) - Nunes, Paulo Reis (2015)
This work tries to recall the memory of the show Jú Onze e 24, directed by Júlio Vilela, and its latest attempts at survival, with its structure and circulation among the theatrical spaces and spaces LGBT in Goiânia, with the main attraction the dragqueens performances. This drags, to carry out the production of a female body translated as assemblies, presented at different mappings. These mappings are understood as flexible operating modes that go or back together. The fact of producing and performing, featuring her performative process, which allowed for a study of the aesthetic transformations in the show, based on studies of performance, queer theory, gender and sexuality. These themes could incite processes of identification and difference about subjects of deviant sexuality, as transvestites and transsexuals who are confused or placed under one label, which confirms that there is confusion regarding the usual drag-queen performance.